PERLINDUNGAN HUKUM INDIKASI GEOGRAFIS HAK KELOMPOK TEKSTIL ALOR IKAT BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Sariyat Muliadin; Happy Yulia Anggraeni (Collegium Studiosum Journal, 2023)
Tenun Alor is one of the results of the crafts of the Alor community whose existence is recognised in the past, has different motifs and different patterns of the products of the other regions, has a particular philosophy in each motive, and is an icon of the region that is frequently used in various activities at the local, national and international level. Unfortunately, the products already known to the market have not been legally protected by intellectual property rights by the State. The aim of this research is to learn about the legal efforts undertaken by the Regional Government in order to promote wider legal protection against Geographical Indications of Alor Tea, as well as to describe the challenges facing to preserve Alor tea. This research is normative. The results of this study show that the Provincial Government has sought to protect Alor Fabrics in the Geographical Indication System because the results of the research show that legal protection is not ideal. One example is the lack of legal certainty about Geographical Indications of Alor fabrics. Furthermore, in order to raise public awareness of the importance of legal protection of Geographical Indications, proper and effective socialization is essential. Effective socialization campaigns should inform people about the importance of protecting Geographical Indications and ofining the quality and originality of products.